Farmers’ social networks’ effects on the sustainable production of fresh apples in China’s Shaanxi province - Khan, Zaid Ashiq; Zhu, Jialin; Khan, Aftab; Koondhar, Mansoor Ahmed; Kakar, Shayan Khan; Ali, Uzair; Tianjun, Liu (Frontiers in Environmental Science, 2023)
Recently, the public and policymakers have acquired knowledge of the detrimental effects of pesticide use in agriculture. These include the threat to the health of chemical applicators and the threat that pesticide residues pose to the safety of food. The present study focuses on the farmers’ social networks from a new perspective, along with the farmers’ concurrent agricultural business and their impact on the farmer’s safe production behavior. The Endogenous Switching Probit Regression model and Binary Probit Group Regression model were employed for the empirical analysis of survey data collected from 585 households in the Xianyang, Yan’an, and Weinan districts of Shaanxi province, China. The results revealed that farmers’ social networks can greatly affect farmers' safe production behavior. Additionally, we noted that the farmers’ social networks may play a positive role in promoting the farmers’ safe production behaviors of both concurrent agricultural business and non-concurrent agricultural business farmers. Moreover, their correlation coefficients were found significant at a confidence level of 5%. Our findings suggest that the government needs to construct social networks among farmers by setting up a communication platform and promoting the acquaintance of safe production through reciprocal culture.